UNFAIR JUDGEMENT IN ANGIE THOMAS’ THE HATE U GIVE - Fanani, Abu; Sodiq, Machfud Mohammad; Muhammad Romdlon, Atiq; Rohman, Abdur; Frank, Ahmad (Lingustic, Literature and English Education, 2025)
There are lots of researches conducting study on Angie Thomas’ the Hate U Give that triggers the researcher to do the study on the same novel. Most of the previous researchers refer to racism as the issue of their study, yet, the researcher comes to the result of the racism indeed with different theory. Using Gramsci’s hegemony theory and close reading method together with dramatic and descriptive approach, the study finds that the unfair judgement by the majority people (the result of racism) brings misery to the minority one, the black community. The unfair judgement refers to the full control of the black organization, the Black Panthers, physical harm, and inhuman treatment. The effects of the unfair judgement refers to the oppression of the black people and the betrayal of the black person.